Crisis inside the crisis: The pandemic of gender violence - Malta, Renata Barreto; Aneas, Tatiana Güenaga; Lisboa, Aline [UNESP]; De Araujo Vieira, Iasmim (FapUNIFESP (SciELO), 2021)
This article aims to analyze how informational texts by Brazilian journalistic and institutional sources present gender violence in the context of Covid-19 pandemic, basing on the premise that social isolation and its political and economic consequences enlarge the threat to human rights. As a method, we have opted for content analysis of the corpus and the discussion of the results is based on gender studies and feminist theory. The main results point to the predominance of journalistic content, with different discursive lines, although domestic violence is central. The absence of sources from women movements, as well as the debate centered on the causes of gender violence which questions the family structure and home as a safe place to confined women is symptomatic of the current scenario of setback, although the pandemic has provided visibility to the problem.
Crise dentro da crise: A pandemia da violência de gênero
Keywords: Content analysis; Covid-19; Gender violence; Informational texts; Social isolation